(untitled) (Al-Mansour Journal, 2022)
The testing methods used to test hypothesis when the data about variables are uncertain, represent fuzzy testing. There are many kinds of fuzzy hypothesis, some of them about percentage of defectives, another related to the ratio of two populations mean or ratio of variances. The testing of fuzzy hypothesis may be simple hypothesis or compound hypothesis, here we introduce a test method for testing hypothesis about the percentage of defectives in certain electrical part produced by certain company, where this produced units are important and introduced with another units to complete the product. The testing of fuzzy hypothesis and everything related to this subject like acceptance and rejection, using procedure of Neyman person as a tool for testing fuzzy hypothesis. All derivations required finding testing rule of fuzzy hypothesis for the data under study. The aim of the research to introduce the statistical testing and statistical inference about parameters of population, and how to make a decision for rejecting or accepting the fuzzy hypothesis for the percentage of defectives of items, are introduced in this research. This paper divided into (3) sections, section (1) contains the theoretical aspects, section (2) contains the application part, the conclusion discussed in section (3).